Genome-wide association and functional studies identify a role for matrix Gla protein in osteoarthritis of the hand. Issue 12 (30th August 2017) - den Hollander, Wouter; Boer, Cindy G; Hart, Deborah J; Yau, Michelle S; Ramos, Yolande F M; Metrustry, Sarah; Broer, Linda; Deelen, Joris; Cupples, L Adrienne; Rivadeneira, Fernando; Kloppenburg, Margreet; Peters, Marjolein; et al.
Abstract : Objective: Osteoarthritis (OA) is the most common form of arthritis and the leading cause of disability in the elderly. Of all the joints, genetic predisposition is strongest for OA of the hand; however, only few genetic risk loci for hand OA have been identified. Our aim was to identify novel genes associated with hand OA and examine the underlying mechanism. Methods: We performed a genome-wide association study of a quantitative measure of hand OA in 12 784 individuals (discovery: 8743, replication: 4011). Genome-wide significant signals were followed up by analysing gene and allele-specific expression in a RNA sequencing dataset (n=96) of human articular cartilage. Results: We found two significantly associated loci in the discovery set: at chr12 (p=3.5 × 10 −10 ) near the matrix Gla protein (MGP) gene and at chr12 (p=6.1×10 −9 ) near the CCDC91 gene. The DNA variant near the MGP gene was validated in three additional studies, which resulted in a highly significant association between the MGP variant and hand OA (rs4764133, Betameta =0.83, Pmeta =1.8*10 −15 ). This variant is high linkage disequilibrium with a coding variant in MGP, a vitamin K-dependent inhibitor of cartilage calcification. Using RNA sequencing data from human primary cartilage tissue (n=96), we observed that the MGP RNA expression of the hand OA risk allele was significantly lowercompared with the MGP RNA expression of the reference allele (40.7%, p<5*10 −16 ). Conclusions: Our results indicate that the association between the MGP variant and increased risk for hand OA is caused by a lower expression of MGP, which may increase the burden of hand OA by decreased inhibition of cartilage calcification.